Conformational analysis of N-methylformamide in ground S0 and excited S1 and T1 electronic states. (July 2016) - Tukachev, N.V.; Bataev, V.А.; Godunov, I.А.
Abstract: For conformers of the N -methylformamide (HCONHCH3 ) molecule, calculations of equilibrium geometry parameters, harmonic vibration frequencies, energy differences and potential barriers to conformational transitions were performed in the ground (S0 ) and lowest excited singlet (S1 ) and triplet (T1 ) electronic states. In the S0 state, the molecule exists in trans and cis stable conformations (having Cs symmetry). Our calculations show that the electronic excitations T1 ←S0 and S1 ←S0 cause changes in the structure of conformers: both HCON and HNCC fragments become pyramidal and rotate around the CN bond. As a result, in each excited electronic state under consideration, there are 12 minima forming six pairs of equivalent conformers separated by relatively small potential barriers. One- and two-dimensional potential energy surface sections corresponding to different intramolecular large-amplitude motions were calculated using the MP2/aug-cc-pVTZ (S0 ) and CASPT2/cc-pVTZ (S1 and T1 ) methods. Anharmonic vibrational problems for large-amplitude motions were solved, and the corresponding frequencies were estimated. Highlights: Six different conformers of N -methylformamide are shown to exist in excited S1 and T1 electronic states. Harmonic and "anharmonic" computations of torsion frequencies in excited electronic states yield relatively similar results. The need in new experimental investigation of vibrational spectrum of this molecule in S0 state is stressed.